2021
DOI: 10.12688/f1000research.23224.2
|View full text |Cite
|
Sign up to set email alerts
|

An environment for sustainable research software in Germany and beyond: current state, open challenges, and call for action

Abstract: Research software has become a central asset in academic research. It optimizes existing and enables new research methods, implements and embeds research knowledge, and constitutes an essential research product in itself. Research software must be sustainable in order to understand, replicate, reproduce, and build upon existing research or conduct new research effectively. In other words, software must be available, discoverable, usable, and adaptable to new needs, both now and in the future. Research software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…Only with an active user group, such frameworks as Wikidata, Pelagios, and other LOD providing systems can become sustainable. This also applies to research software [153]. Regarding the infrastructure side, a commitment by national and international funding bodies is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Only with an active user group, such frameworks as Wikidata, Pelagios, and other LOD providing systems can become sustainable. This also applies to research software [153]. Regarding the infrastructure side, a commitment by national and international funding bodies is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Arguments for FLOSS in a research context and common misconceptions have been discussed, for instance, in [37]. Adopting a FLOSS license [14,37] (in contrast to a proprietary software license) implies that the software is modifiable (derivable) and redistributable which can be argued to be an essential prerequisite for a sustainable research software landscape [7,13,24,28,38,39]. Moreover, it can be argued that out of ethical responsibility, research software that is developed with the help of public funding should be publicly available [28].…”
Section: Free and Open-source (Research) Softwarementioning
confidence: 99%
“…Adopting a FLOSS license [14,37] (in contrast to a proprietary software license) implies that the software is modifiable (derivable) and redistributable which can be argued to be an essential prerequisite for a sustainable research software landscape [7,13,24,28,38,39]. Moreover, it can be argued that out of ethical responsibility, research software that is developed with the help of public funding should be publicly available [28]. Besides the software used specifically for research activities, employing FLOSS products is equally important for all infrastructure components [13].…”
Section: Free and Open-source (Research) Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…However, research publications that present novel results remain the key indicator of credit and acknowledgment of scholarly contributions. Previous work has described why this model of research publication is incompatible with a current ecosystem where significant effort is devoted to developing software tools in order to produce novel research results [2,10]. Previous scientometric work has also shown that software is often cited in traditional research publications [9,11], but tracing and identifying these software mentions is difficult due to disparate practices in publishing and archiving research software [7,14].…”
Section: Introductionmentioning
confidence: 99%